2017
DOI: 10.1007/s11886-017-0833-2
|View full text |Cite
|
Sign up to set email alerts
|

Can We Improve the Outcomes of Multivessel Disease Using Modified SYNTAX and Residual SYNTAX Scores?

Abstract: Recently randomized and observational studies demonstrated using functional flow reserve analysis, residual Syntax score risk, or residual ERACI score after PCI that a reasonably incomplete revascularization was associated with good long-term outcome and low events rate at follow-up. In the ERACI IV study, which included patients with multiple vessel disease and left main, all intermediate lesions and severe lesions in small vessels were excluded from the revascularization strategy, and the 3-year follow-up re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 35 publications
0
9
0
3
Order By: Relevance
“…Recently, ERACI IV investigators reported that a conservative strategy during DES deployment was associated with a low number of adverse events at follow up. Moreover, they found that residual risk score built following such PCI strategy, had more correlation with the late outcome that the original residual Syntax score has had 19,24 . Accordingly, in the present study, we also found large discrepancies in baseline and residual risk score between both methods of measurements, however, we don't know if the above benefits would also be present in patients treated with BMS design.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, ERACI IV investigators reported that a conservative strategy during DES deployment was associated with a low number of adverse events at follow up. Moreover, they found that residual risk score built following such PCI strategy, had more correlation with the late outcome that the original residual Syntax score has had 19,24 . Accordingly, in the present study, we also found large discrepancies in baseline and residual risk score between both methods of measurements, however, we don't know if the above benefits would also be present in patients treated with BMS design.…”
Section: Discussionmentioning
confidence: 99%
“…El score de calcio, un subrogante de la carga de placa ateroesclerótica, es una herramienta segura (<1 mSv de dosis de radiación efectiva) que no requiere contraste, agujas, ni preparación alguna. Su valor pronóstico ha sido demostrado de forma consistente en una enorme cantidad de estudios multicéntricos de gran tamaño y seguimiento de hasta 15 años, independiente del sexo, etnia, factores de riesgo y de las pruebas funcionales [22][23][24] . Además, el score de calcio promueve cambios favorables en el estilo de vida, una mejor adherencia al tratamiento y una mejor selección de los pacientes con indicación de aspirina y estatinas [25][26][27][28] .…”
Section: Revista Argentina De Cardioangiología Intervencionista 2017;unclassified
“…Múltiples estudios han evaluado la superioridad de la OCT con respecto al IVUS en la determinación de mala aposición del stent en el seguimiento y posintervención inmediata 21,22 . Esta puede ser un gran aporte de la OCT al mundo de la revascularización por stent, debido a que efectos como la mala aposición del stent han sido ya relacionados a mayores tasas de reestenosis y stent trombosis en estudios realizados por IVUS [23][24][25] Con lo evaluado hasta el momento podemos ver entonces algunas limitaciones que oscurecen el potencial impacto clínico en la pesquisa invasiva de la placa vulnerable: la alta prevalencia de las placas de alto riesgo o cómo no todos los FACF se rompen y no muchas rupturas de placa desencadenan eventos clínicos. Otra desventaja está en que alrededor de un 40% de las trombosis agudas no tienen como sustrato la ruptura de placa sino otros mecanismos fisiopatológicos.…”
Section: En El Seguimiento Luego De Angioplastia Coronariaunclassified
See 1 more Smart Citation
“…Critical stenosis of the unprotected left main (ULM) have a detrimental impact on short and long term survival . Surgical revascularization has been for many years the first‐choice treatment, while in the last decade percutaneous coronary intervention (PCI) has affirmed itself as a viable option, showing similar long‐term results as compared to coronary artery bypass graft, especially in patients with low‐intermediate Syntax score values .…”
Section: Introductionmentioning
confidence: 99%